La naissance de l'anti-hégélianisme Louis Althusser et Michel Foucault, lecteurs de Hegel - Vuillerod, Jean-Baptiste (La croisée des chemins, 2022)
This book provides a counter argument against simplistic interpretations of the anti-Hegelianism that marks Louis Althusser and Michel Foucault's works in the 1960s. Probing into the early works of these philosophers, it unearths Hegel's fundamental influence on the development of their philosophical approaches. Through a meticulous examination of Althusser and Foucault's intellectual journeys, supported by numerous archival materials, Vuillerod seeks to show how the basis of their philosophies was formed through an immanent critique of Hegelianism. This provides a whole new angle on the change that occurred in French philosophy during the 1960s, with its slew of new outlooks on reason, subject, and history. The book argues that, far from being unilaterally against Hegel, this great reinvention of philosophy was, in fact, steeped in conflictive yet fruitful dialogue with Hegel's work. This radically transforms our idea of French philosophy as a whole over the latter half of the twentieth century. Jean-Baptiste Vuillerod is an associate professor and doctor of philosophy. His published work includes Hegel féministe. Les aventures d'Antigone (Vrin, 2020), Adorno et la domination de la nature (Amsterdam, 2021) and the article "Spinoza as a revolutionary? A reading based on Gilles Deleuze" in Archives de Philosophie (2021). He also edited Jacques Martin's text, L'individu chez Hegel (ENS Éditions, 2020).